2018
DOI: 10.1080/14656566.2018.1459567
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir + velpatasvir + voxilaprevir for the treatment of hepatitis C infection

Abstract: Introduction Hepatitis C is a disease with a significant global impact. Over the last several years, the treatment of the disease has been revolutionized. Therapy has transformed over the last several years with the approval of second generation direct acting antivirals, and currently utilized medications for the treatment of hepatitis C are significantly more efficacious with better safety profiles than previously approved treatments. Treatment for individuals who have failed therapy on direct acting antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, treatment strategy including its antiviral drugs and treatment duration could overcome other factors causing poor prognosis ( Sarrazin and Zeuzem, 2010 ; Sarrazin, 2016 ; Sarrazin et al, 2016 ; Bartolini et al, 2017 ; Paolucci et al, 2017 ; Pérez et al, 2017 ; Zeuzem et al, 2017 ; Aldunate et al, 2018 ; Dietz et al, 2018 ; Esposito et al, 2019 ; Sayan et al, 2020 ). Sofosbuvir (PSI-7977 and GS-7977), is a very potent viral RdRp (NS5B) inhibitor with a pan-genotypic effect on HCV, without issues of viral resistance ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Gane et al, 2017 ; Cory et al, 2018 ; Sorbo et al, 2018 ). It is a prodrug of 2′-deoxy-2′-fluoro-2′-C-methyluridine monophosphate which should be changed to its activated form (2‘- C-methyl group) in the liver and acts as a chain terminator ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Lawitz et al, 2014 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Bagaglio et al, 2018 ; Cory et al, 2018 ; Sorbo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, treatment strategy including its antiviral drugs and treatment duration could overcome other factors causing poor prognosis ( Sarrazin and Zeuzem, 2010 ; Sarrazin, 2016 ; Sarrazin et al, 2016 ; Bartolini et al, 2017 ; Paolucci et al, 2017 ; Pérez et al, 2017 ; Zeuzem et al, 2017 ; Aldunate et al, 2018 ; Dietz et al, 2018 ; Esposito et al, 2019 ; Sayan et al, 2020 ). Sofosbuvir (PSI-7977 and GS-7977), is a very potent viral RdRp (NS5B) inhibitor with a pan-genotypic effect on HCV, without issues of viral resistance ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Gane et al, 2017 ; Cory et al, 2018 ; Sorbo et al, 2018 ). It is a prodrug of 2′-deoxy-2′-fluoro-2′-C-methyluridine monophosphate which should be changed to its activated form (2‘- C-methyl group) in the liver and acts as a chain terminator ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Lawitz et al, 2014 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Bagaglio et al, 2018 ; Cory et al, 2018 ; Sorbo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sofosbuvir (PSI-7977 and GS-7977), is a very potent viral RdRp (NS5B) inhibitor with a pan-genotypic effect on HCV, without issues of viral resistance ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Gane et al, 2017 ; Cory et al, 2018 ; Sorbo et al, 2018 ). It is a prodrug of 2′-deoxy-2′-fluoro-2′-C-methyluridine monophosphate which should be changed to its activated form (2‘- C-methyl group) in the liver and acts as a chain terminator ( Murakami et al, 2010 ; Sofia et al, 2010 ; Poordad and Dieterich, 2012 ; Lawitz et al, 2014 ; Stedman, 2014 ; Tong et al, 2014 ; Costantino et al, 2015 ; Gallego et al, 2016 ; Bagaglio et al, 2018 ; Cory et al, 2018 ; Sorbo et al, 2018 ). Since its discovery, SOF has dramatically changed the treatment outcome of patients with HCV infection who were infected with hard-to-treat genotypes (1 and 3), cirrhosis, and previous history of treatment ( Sofia et al, 2010 ; Lawitz et al, 2014 ; Stedman, 2014 ; Gallego et al, 2016 ; Gane et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Velpatasvir is a pangenotypic inhibitor; compared to the rest, this drug has a higher resistance barrier. These drugs act by the same mechanism of action, preventing the function of the NS5A protein and the formation of a protein complex necessary for the initiation of viral replication and influencing the subsequent assembly of the virion [ 27 , 28 , 29 , 30 ]. Pibrentasvir, Velpatasvir and their combinations will be addressed later.…”
Section: Resultsmentioning
confidence: 99%
“…Velpatasvir (VLP) is a direct-acting antiviral agent (DAA) against hepatitis C virus (HCV) [40]. VLP is a novel HCV NS5A inhibitor with potent antiviral activity against genotype 1 to 6 replicons.…”
Section: Introductionmentioning
confidence: 99%
“…VLP is defined as a Biopharmaceutical Classification System (BCS) class IV drug, with low aqueous solubility and low permeability. It is soluble at pH 1.2, sparingly soluble at pH 2, and practically insoluble at pH > 5 [40,41]. This behaviour of the drug is responsible for its poor bioavailability as it is reported that in a fasting state, the pH of the stomach lies between 1.3 to 2.5 and raises to 4.5 to 5.8 within an hour after eating [42].…”
Section: Introductionmentioning
confidence: 99%